Analisis Strategi Pemasaran Pada Perusahaan Freight Forwarding PT. Logwin Air & Ocean Indonesia - Rizky Syafputra; Sri Fauziah; Mardiyanto Amir; Yoyoh Cikayanti (Journal on Education, 2023)
In connection with the very high demand for market shipping services, PT Logwin Air & Ocean Indonesia requires the right marketing strategy so that the company can survive and develop. Therefore, the purpose of this study is to analyze the marketing strategy which is an important tool in identifying the 4P Marketing Mix and STP Analysis. So that the company can formulate a competitive strategy in its business. The results of the analysis based on the data obtained, that the services offered by PT Logwin Air & Ocean Indonesia are very good if developed and marketed both domestically and abroad. From the results of this marketing strategy analysis, there are several things that need to be managed and anticipated by the management of PT Logwin Air and Ocean Indonesia. The main key for a company to break through the domestic and foreign markets is to continue to adapt to the target market. No less important is the inclusion of technology, especially social media is the main factor that supports success in keeping up with the evolving times.